Pengaruh Automatic Change Over Switch Terhadap Peningkatan Keandalan Gardu Distribusi T3-200A/1 Penyulang PLR-04 - Tri Irianto Tjendrowasono; Supriyana Nugroho; Ni Kadek Devi Suyastini (Jurnal FORTECH, 2023)
The process of distributing electrical energy has the potential to cause disturbances that can occur due to natural disturbances, disturbances to electrical equipment, disturbances at the generating center, transmission lines, and disturbances in the distribution network that can disrupt the reliability and service quality of the distribution of electrical energy. The quality of reliability can be rated by the length of outages, which can be determined using the System Average Interruption Duration Index (SAIDI), and how often blackouts occur in one unit of time, which can be determined using the System Average Interruption Frequency Index (SAIFI). In maintaining the reliability of electrical energy, additional equipment is needed that is capable of supplying backup energy to the load when a disturbance occurs, namely the Automatic Change Over Switch (ACOS). ACOS is a device that works automatically for the process of maneuvering the network from two voltage sources to maintain electricity availability without having to have long blackouts due to disturbances or loss of voltage at the main source. The use of the Automatic Change Over Switch (ACOS) is proven to be able to increase the reliability of electrical energy at distribution substation T3-200A/1 feeder PLR-04 by reducing the length of time outages (SAIDI) and reducing the frequency, because customers don't feel outages when the disturbance occurs. In addition, the use of Automatic Change Over Switch (ACOS) can also reduce the energy not supplied (ENS)